Female fecundity variation affects reproducibility of experiments on host plant preference and acceptance in a phytophagous insect. Issue 1849 (22nd February 2017) - Schäpers, Alexander; Petrén, Hampus; Wheat, Christopher W.; Wiklund, Christer; Friberg, Magne
Abstract : Reproducibility is a scientific cornerstone. Many recent studies, however, describe a reproducibility crisis and call for assessments of reproducibility across scientific domains. Here, we explore the reproducibility of a classic ecological experiment—that of assessing female host plant preference and acceptance in phytophagous insects, a group in which host specialization is a key driver of diversification. We exposed multiple cohorts of Pieris napi butterflies from the same population to traditional host acceptance and preference tests on three Brassicaceae host species. Whereas the host plant rank order was highly reproducible, the propensity to oviposit on low-ranked hosts varied significantly even among cohorts exposed to similar conditions. Much variation could be attributed to among-cohort variation in female fecundity, a trait strongly correlated both to female size and to the size of the nuptial gift a female receives during mating. Small males provide small spermatophores, and in our experiment small females that mated with small males had a disproportionally low propensity to oviposit on low-ranked hosts. Hence, our results provide empirical support to the theoretical prediction that female host utilization is strongly affected by non-genetic, environmental variation, and that such variation can affect the reproducibility of ecological experiments even under seemingly identical conditions.